BIDAK BACA: MEDIA PEMBELAJARAN INTERAKTIF BERMUATAN KEARIFAN LOKAL UNTUK MENINGKATKAN KEMAMPUAN MEMBACA - Adi Iwan Hermawan; Ernawati Simatupang; Megie Syauta (Jurnal Muara Pendidikan, 2023)
Initial reading ability level at SD Inpress 38 Matawolot Kab. Sorong is still quite low. An alternative solution to improve initial reading skills is to develop educational reading media containing local wisdom. This research uses quantitative methods. Based on the ADDIE model development method (Analysis, Design, Development, Implementation, Evaluation). This research was conducted at SD Inpress 38 Matawolot District. Shove. With a total of 19 students. Data collection techniques in this research are observation, interviews and documentation techniques. Data was collected through validation sheets from material experts, media experts, language experts, and teacher responses. The results of testing the effectiveness of reading learning media have proven to be able to improve the learning outcomes of class 1 students. This can be explained by the N-gain score of 0.4 which is included in the medium category, namely in the range 0.3 – 0.7. The results of this research show that the reading media educational media containing local wisdom is very valid and practical for use in initial reading learning at SD Inpress 38 Matawolot District Sorong.